Visitor Prediction Decision Support System at Dieng Tourism Objects Using the K-Nearest Neighbor Method - Eko Hari Rachmawanto; Christy Atika Sari; Heru Pramono; Wellia Shinta Sari (Journal of Applied Intelligent System, 2022)
A tourist target is anything that attracts a visitor or tourist to come to visit a place or area. Tourism goods play an important role in a country or region, becoming a source of national foreign exchange, increasing human resources, and improving the economy of surrounding communities. The problem posed in this study is how to implement a decision support system in predicting visitor numbers for Dieng tourists using the k-nearest neighbor method. The purpose of this study is to help the local government and surrounding communities to improve facilities such as restaurants, places of worship, parking lots, clean toilets so that tourists can feel safe and comfortable when visiting Dieng. Helps manage tourism targets. is what you give. These attractions using a decision support system as a process to predict visitors. The number of visitors who visited in December 2017 was 421,394, which serves as a reference for predicting the number of visitors who will visit Dieng in the following year. The predicted result is 29569.25 visitors with a parameter value of k = 8 and a minimum RMSE value of k = 1/0.